Performance and Carcases Percentage of Pekin Duck Supplied with Sago Pith Silage as An Energy Source - Abrani Sulaiman; Harry Wijayanto; Khairil Anwar; Eka Sumantri; Danang Biyatmoko (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2022)
The purpose of this study was to determine the optimal level of use of sago pith silage to replace rice bran in the ration on the production performance of male Peking ducks. The research treatments included: T0 = No sago pith silage (control), T1 = Use of 5% sago pith silage in the ration, T2 = Use of 10% sago pith silage in the ration, T3 = Use of 15% sago pith silage in the ration, T4 = Use of sago pith silage 20% in the ration. The experimental diet contained 16% crude protein and 3000 kcal/kg metabolizable energy. The Pekin ducks used in this experiment were 2 weeks old. The research design used was a complete randomized design using five feeding treatments, five replications, and four ducks per replication pens. The parameters measured were feed intake, weight gain, body weight, feed conversion, the percentages of carcass, giblet, and abdominal fat at 8 weeks of age. The results showed that the use of sago pith silage had no significant effect on feed consumption, weight gain, body weight, feed conversion, and the percentages of carcass and giblet. However, the use of sago pith silage increased abdominal fat. It can be concluded that the use of sago pith silage up to 20% to replace rice bran in the ration has no negative effects on the performance and carcass quality of ducks.